VISIBLE LANGUAGE-COVERT POLICY: AN INVESTIGATION OF LANGUAGE POLICY DOCUMENTS AT EMI UNIVERSITIES IN TURKEY - Ali Karakas (Informascope, 2018)
As universities attempt to change their medium of instruction from the local languages to English and become more international by recruiting international students and teaching staff, their academic English language policies and practices appear to be more prominent. The use of English in higher education as the medium of instruction and the increasing cultural and linguistic mixture on campuses make EMI universities a fruitful ground to explore issues of language policy and practice. This paper explores the academic English language policies and practices of three EMI universities in Turkey. Applying a combination of qualitative content analysis and negative analysis, I seek to find out institutions' overall orientation to English in their policy documents. The analysis shows that English is overtly pronounced as the official language of the institutions, yet the kind of English required remains considerably covert. However, the analysis of policy mechanisms further indicate that each university orients to a particular standard (native) English by implication as the appropriate kind of academic English. Additionally, such normative orientations seem to be guided by several dynamically intertwined ideologies. These results suggest that language-wise, universities' academic language policies are in need of immediate and drastic revision.